Robot‐assisted radical prostatectomy: learning rate analysis as an objective measure of the acquisition of surgical skill - Sammon, Jesse; Perry, Andrew; Beaule, Lisa; Kinkead, Thomas; Clark, David; Hansen, Moritz (BJU international, 2010)
Study Type – Therapy (case series) Level of Evidence 4 OBJECTIVE To adapt an industrial definition of learning‐curve analysis to surgical learning, and elucidate the rate at which experienced open surgeons acquire skills specific to robot‐assisted radical prostatectomy (RARP) at a community‐based medical centre. PATIENTS, SUBJECTS AND METHODS The total procedure time (TPT) of the first 75 RARPs, performed by three surgeons experienced with retropubic RP, was analysed to determine the point at which their learning rate stabilised. Operative characteristics were compared before and after this point to isolate the plateau of learning rate as a mark of acquiring surgical skill. The operative characteristics examined were TPT, estimated blood loss (EBL), bladder neck contractures (BNC), positive margins (PM) and length of hospital stay (LOS). RESULTS The mean rate of TPT decrease, for procedures 1–75, was 13.4% per doubling of RARPs performed. After the first 25 procedures the TPT decreased at a rate of 1.8% per doubling, not significantly different from 0 (P > 0.05). There was no significant difference between procedures 1–25 and 26–75 in rates of EBL, BNC and PM. There was a significant change for all surgeons in TPT, with a mean of 303.1 min (RARPs 1–25) vs 213.6 min (26–75) (P < 0.001), and LOS, of 2.1 days (1–25) vs 1.4 days (26–75) (P < 0.001). CONCLUSIONS An industrial definition of learning‐curve analysis can be adapted to provide an objective measure of learning RARP. The average learning rate for RARP was found to plateau by the 25th procedure. Also, the learning rate plateau can serve as an objective measure of the acquisition of surgical skill.